2015
DOI: 10.1371/journal.pntd.0003561
|View full text |Cite
|
Sign up to set email alerts
|

Development of a pHrodo-Based Assay for the Assessment of In Vitro and In Vivo Erythrophagocytosis during Experimental Trypanosomosis

Abstract: Extracellular trypanosomes can cause a wide range of diseases and pathological complications in a broad range of mammalian hosts. One common feature of trypanosomosis is the occurrence of anemia, caused by an imbalance between erythropoiesis and red blood cell clearance of aging erythrocytes. In murine models for T. brucei trypanosomosis, anemia is marked by a very sudden non-hemolytic loss of RBCs during the first-peak parasitemia control, followed by a short recovery phase and the subsequent gradual occurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 44 publications
0
44
0
2
Order By: Relevance
“…Human erythrocytes incubated with EVs showed an increase in membrane rigidity as indicated by a narrowing and shift of the emission spectra of Laurdan towards shorter wavelengths (Figure 6D). Recently it has been shown that erythrocyte lipid composition was altered during trypanosomiasis, and these cells were preferentially phagocytosed by myeloid cells (Stijlemans et al, 2015). Incorporating parasite lipid via EV fusion may explain altered erythrocyte lipid composition.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Human erythrocytes incubated with EVs showed an increase in membrane rigidity as indicated by a narrowing and shift of the emission spectra of Laurdan towards shorter wavelengths (Figure 6D). Recently it has been shown that erythrocyte lipid composition was altered during trypanosomiasis, and these cells were preferentially phagocytosed by myeloid cells (Stijlemans et al, 2015). Incorporating parasite lipid via EV fusion may explain altered erythrocyte lipid composition.…”
Section: Resultsmentioning
confidence: 99%
“…These host immune responses have been implicated in the pathology of trypanosomiasis-associated anemia (Stijlemans et al, 2015). Anemia is markedly severe during acute infection and is the major cause of cattle death due to Nagana (Naessens, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transfer of VSG to host erythrocytes was previously observed by [5] but the mechanism behind it and its functional relevance remained a mystery. Szempruch et al demonstrate that fusion of EVs with host erythrocytes affects erythrocyte rigidity and size and postulate that this results in preferential clearance by host myeloid cells [6], though this is not tested directly. Consistent with this model, the intravenous injection of parasite EVs into naïve mice results in a 5–10% decrease in the number of host erythrocytes within 1hr, demonstrating a potential role for parasite EVs in infection-associated anemia.…”
mentioning
confidence: 99%
“…Consistent with this model, the intravenous injection of parasite EVs into naïve mice results in a 5–10% decrease in the number of host erythrocytes within 1hr, demonstrating a potential role for parasite EVs in infection-associated anemia. The transfer of VSG from the parasite surface to the recipient erythrocyte raises the possibility that erythrocytes could become targets of antibody responses directed against parasite VSGs, which might also be expected to cause increased erythrocyte clearance, though [6] show preferential clearance of trypanosome-altered erythrocytes even in uninfected mice. It remains to be seen whether T. brucei EVs fuse with other host cell types, and what, if any, modulatory effect they have.…”
mentioning
confidence: 99%